The assassination of Olof Palme: evidence and ideology - Jenkins, Philip (Contemporary crises, 1989)
In February 1986, the Swedish premier was assassinated in a crime of political violence that remains unsolved at the time of writing. The present paper examines the various explanations that were proposed for this act, both in Sweden and in other Western countries. It will be shown how these explanations changed as the scope of the investigation grew in complexity and how investigators deviated more and more sharply from the ‘official’ Western view of terrorism. From early suspicion of traditional villains - Middle Eastern separatists or German leftists - attention has focused more recently on very different candidates, in Swedish business and intelligence circles. The aim of the paper is neither to solve the crime nor to produce any new evidence, but to study the changing ideological assumptions of the investigative process, particularly when dealing with sensitive political offenses.